2023
DOI: 10.21203/rs.3.rs-2802306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccination with intravenous BCG protects macaques with pre-existing SIV infection from tuberculosis

Abstract: Tuberculosis (TB) is the most common cause of death in people living with HIV. BCG delivered intradermally (ID) is the only licensed vaccine to prevent TB. However, it offers little protection from pulmonary TB in adults. Intravenous (IV) BCG, but not ID BCG, confers striking protection against Mycobacterium tuberculosis (Mtb) infection and disease in rhesus macaques. We investigated whether IV BCG could protect against TB in macaques with a pre-existing SIV infection. There was a robust influx of airway T cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…The data do not rule out the possibility that through repeated boosting (25) or the use of a specially engineered bacterial strain (36) protection against COVID-19 could be generated through conventional ID or SC vaccination although it is likely that such resistance would involve a different mechanism. There is currently considerable interest in the possible use of IV administered BCG for vaccination against M. tuberculosis because of its ability to confer sterile immunity against this important pathogen in rhesus monkeys (11,13). This has stimulated efforts to develop attenuated BCG mutants (e.g.…”
Section: Discussion and Translational Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data do not rule out the possibility that through repeated boosting (25) or the use of a specially engineered bacterial strain (36) protection against COVID-19 could be generated through conventional ID or SC vaccination although it is likely that such resistance would involve a different mechanism. There is currently considerable interest in the possible use of IV administered BCG for vaccination against M. tuberculosis because of its ability to confer sterile immunity against this important pathogen in rhesus monkeys (11,13). This has stimulated efforts to develop attenuated BCG mutants (e.g.…”
Section: Discussion and Translational Implicationsmentioning
confidence: 99%
“…In the second report, Darrah and colleagues showed that IV in contrast to SC administered BCG induces sterile immunity against M. tuberculosis (Mtb) challenge in a rhesus monkey model (11), a dramatic finding that the authors attributed to the direct targeting of the lung and the induction of a strong local memory T cell response when the vaccine is given by this route (12). Recent studies indicate that in macaques such resistance can persist after the clearance of culturable BCG bacilli (13). Nevertheless, the contribution of BCG stimulated innate immune mechanisms to this striking protection is at present unclear.…”
Section: Introductionmentioning
confidence: 99%